Phyllochron estimates on agronomic potential and physiological quality of millet (Colloquium Agrariae. ISSN: 1809-8215, 2023)
Millet is largely explored for a diversity of applications. The use of millet high-quality seeds is essential to increase grain yield. Accordingly, the purpose of this study was to evaluate the yield variability of millet plants from higher and lower-quality seeds in the expression of dry matter yield parameters. The study was conducted in the experimental and didactic area of IFRS - campus Ibirubá, Rio Grande do Sul, Brazil, with a completely randomized design. The treatments were plants from seeds of higher (HQS) and lower (LQS) quality and two season crops (2015/16 and 2017/18) in eight replications. The emergence speed was applied to identify plants from seeds of different qualities. The phyllochron, leaf number, height, stem diameter, number of nodes, and dry mass yield were the agronomic components evaluated for this study. Meteorological information was used to calculate phyllochron, water deficit, and average temperature. The collected data were submitted for analysis of variance and the Tukey test at a 5% probability of error. The HQS expressed lower phyllochron and most significant agronomic components. Furthermore, the 2015/16 crop had the lowest water deficit and obtained the best results.